Преобразователь частоты с промежуточным звеном высокой частоты для автономной системы электроснабжения - Коробков, Д.В.; Макаров, Д.В.; Решетников, А.Н.; Машинский, В.В. (Технічна електродинаміка, 2012)
The design principles of frequency converter with intermediate high frequency link for stand-alone power system are featured. The distinctive feature of made decisions consist of module aufbau principle of high frequency blocks of power circuit with working frequencies higher than 100 kHz and of high-performance microcontroller and EPLD application.